I, you, and the word God : finding meaning in the Song of Songs - Zhang, Sarah (Winona Lake, Indiana : Eisenbrauns, 2016)
"I, You, and the Word "God" introduces the approach of lyrical ethics, inspired by Emmanuel Levinas's ethical-phenomenological philosophy. Through the optics of lyrical ethics, the reader discovers how the ancient erotic poems of the Song of Songs bear ethical and theological significance for contemporary readers. Levinas's intertwined concepts--oneself qua sensibility, otherness perceived through responsibility, and transcendence embodied in one's love for the other--reveal themselves as lyrical colors woven into the fabric of Song 4:1-7, 5:2-8, and 8:6. More importantly, Levinas's understanding that poetic language breaks the tautology of logocentric discourse and gestures to the outside of consciousness provides the theoretical ground for the listener to solicit meaningfulness from the Song. Through this lyrical reading of the selected poetic units, the book demonstrates that the traditional interpretive methods of representative description, narrative paraphrase, and thematic distillation fail to encounter the otherness of poetry. In contrast, lyrical ethics pays attention to that which transcends consciousness: the awakening of the reader's subjectivity, the saying underlying the said, the sound of the sense, and the invisibility of the visible. The Song so caressed reveals in human love the purposelessly purposive encounter with God"--
Includes bibliographical references and indexes.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Bible. -- Criticism, interpretation, etc; Bible; RELIGION / Biblical Studies / Old Testament; RELIGION / Biblical Studies / Wisdom Literature; Criticism, interpretation, etc; Electronic books